A Dynamic Software Startup Competency Model - Assyne, N.; Wiafe, I. (My University, 2019)
Current literature suggests that the engineering activities of software engineering and software startup engineering differ. Thus, there is a need to elicit competencies specific to software startup engineering. This paper proposes a model that provides the various types of competencies and their respective relevance at the various stages of software startup evolution.
Research Article
Keywords: Startups; Innovation; startup engineering; startup evolution